Hypertextual Reading in a Context of Academic Literacy: A Case Study - Aillon Neumann, Mariana Sofía; Figueroa Sandoval, Beatriz Eugenia; Neira Martínez, Angie Carolina (Revista Complutense de Educación, 2015)
Considering the massive access and use of ICTs the demand for educational applications has increased. In this particular scenario interdisciplinary teams have been generated and time and resources have been allocated for the creation of multimodal softwares and the management of the hypermedia and the internet to train students on how to read, write and communicate online. Results not only show their efficiency in language teaching, but also in digital literacy, in the different educational levels. This background has aroused the interest of specialists related to the hypertextual academic literacy environment to meet the needs of higher education students with respect to the use of internet, especially in the procurement of information and generation of knowledge. To be able to suggest solutions with respect to this particular situation it is necessary to identify on first place the cognitive processes which is developed by the individuals in their interaction with the web. Regarding this challenge, the present study considers the findings of a case study performed with the assistance of the Netsupport School Software that describes the practice of hypertextual reading, carried out by a group of students belonging to a Master´s Degree in Education program. The research work shows the identification and the analysis of cognitive processes developed during the performance of a particular task related to the search of information, selection and association of information in internet for a specific subject matter of a Post-Degree program in Education. Results suggest that the development of hyper-reading practices is essential to be able to face academic duties requested by current post-graduate studies and that an imperfect management of hyper-reading practices will negatively impact on students learning.
Keywords: academic literacy; reading; hypertext; case study